Energy Potentials and Carbon Intensity for Bio-natural Gas from Livestock Manure in China - Yajie Yin; Xiaoping Jia; Zhiwei Li; Raymond R. Tan; Jun Wan; Fang Wang (Chemical Engineering Transactions, 2023)
Bio-natural Gas (BNG) from livestock manure (BNGLM) is a potential alternative energy source that can yield significant resource and environmental benefits. Energy potentials and carbon intensity differences in livestock manure utilization may exist in provincial areas. The spatial and temporal distribution characteristics for the BNG potentials are analyzed. A life-cycle carbon emission accounting model for carbon intensity was proposed. The results show that with the increase of scale and intensification of animal husbandry, the BNG potential is increasing. The potentials vary greatly among provinces. The annual carbon emission reduction potential from BNGLM reached 1.25 Gt. The proposed energy potential, its spatial characteristics, and carbon emission reduction measurement are expected to provide better support for enhancing specific regional plans for waste manure utilization and development.